The methodological quality assessment of systematic reviews/meta-analyses of chronic prostatitis/chronic pelvic pain syndrome using AMSTAR2 - Xin Guan; Yongfeng Lao; Jian Wang; Yanan Wang; Yanan Bai; Xiaolong Li; Shuai Liu; Zewen Li; Fuhan Li; Zhilong Dong (BMC Medical Research Methodology, 2023)
Abstract Background This study aimed to assess the methodological quality of the systematic reviews/meta-analyses (SRs/MAs) of chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) using A Measurement Tool to Assess systematic Reviews (AMSTAR2) and to explore the potential influencing factors. Methods PubMed, EMBASE and Cochrane Library databases were searched for relevant studies. AMSTAR2 was used for evaluating the methodological quality of eligible SRs/MAs. Differences between methodological characteristics of SRs/MAs were compared using chi-square tests. The intra-class correlation coefficient (ICC) was used to assess reviewer agreement in the pre-experiment. Multivariate regression analysis was used to identify potential factors affecting methodological quality. Results A total of 45 SRs/MAs were included. After AMSTAR2 evaluation, only two (4.4%) of 45 SRs/MAs were moderate, three (6.7%) were rated as low quality, and the remainder 40 (88.9%) were rated as critically low quality. Among the 16 items of AMSTAR2, item 3 and item 10 had the poorest adherence. Item 4 received the most significant number of "Partial Yes" responses. Univariable analysis indicated that there were significant differences in methodological quality in SRs between different continents (P = 0.027) as well as between preregistered SRs and those that were not (P = 0.004). However, in multivariate analysis, there was no significant association between methodological quality and the following research characteristics: publication year, continent, whether reporting followed Preferred Reporting Items for Systematic Reviews (PRISMA), preregistration, funding support, randomized controlled trials (RCT) enrollment, whether SR was published in the Cochrane Database of Systematic Reviews (CDSR), and whether with meta-analysis. Additionally, subgroup analysis based on interventional SRs/MAs showed that continent was independently associated with the methodological quality of SRs/MAs of CP/CPPS via univariable and multivariate analysis. Conclusions Our study demonstrates that the methodological quality of SRs/MAs of CP/CPPS was generally poor. SRs/MAs of CP/CPPS should adopt the AMSTAR2 to enhance their methodological quality.